ANALISIS MANAJEMEN PELAKSANAAN PROGRAM PEMBERANTASAN DEMAM BERDARAH DENGUE - Hayati, Nur; Perdana Poetra, Ricky; Inayati, Inna Noor; Hastuti, Hastuti; Andriani, Veby (Ensiklopedia of Journal, 2024)
Based on an initial survey in the Tanjung Morawa Puskesmas working area, it shows that the implementation of the Dengue Fever Eradication Program (P2DBD) has not reached an optimal level. The problems identified include the lack of involvement of health workers in running the P2DBD Program, delays in reporting the results of P2DBD activities, and lack of facilities and infrastructure needed to run the program. The purpose of the study was to determine the management implementation of the dengue hemorrhagic fever eradication program. The research used an analytical qualitative method conducted at the Tanjung Morawa Health Center to 5 informants. The results showed that inputs include insufficient human resources, the infrastructure used is still incomplete, the funds come from the Health Operational Assistance and the method according to the technical guidelines. The process of activities from the implementation of the P2DBD Program still has activities that have not been carried out optimally. It is recommended that the Tanjung Morawa Health Center can increase the human resources involved in the P2DBD program, equip facilities and infrastructure according to the needs in implementing the P2DBD program, improve a good and effective supervision, control and evaluation system in every process of program implementation by making various observations directly in the field so that mistakes made by officers can be corrected immediately.Keywords: Puskesmas, P2DBD, HR